Rzeczpospolita Obojga Narodów we wczesnych angielskich publikacjach prasowych (1620‑1642) - Kalinowska, Anna (Odrodzenie i Reformacja w Polsce, 2013)
Polish‑Lithuanian Commonwealth in English corantos (1620‑1642) The article discusses news reports from or dealing with Polish‑Lithuanian Commonwealth published in English corantos in the 1620s and 1630s. Analysis of news items published in corantos, their content, number, etc. show that corantos’ publishers and English readers were especially interested in military and political news, for example on Polish‑Turkish and Polish‑Swedish conflicts, and internal political situation including Sigismund III’s relations with the opposition, and some of the reports were very detailed and reliable. The large numbers of reports datelined from Vienna, Prague and Silesia and the wide international context of Polish news could have resulted from the fact that the situation in the Habsburg dominions was in the focus of English readers’ interest. The presence of Polish news in the corantos proves also that by the 1620s, in spite of all possible impediments, Poland‑Lithuania was already a part of the larger pan‑European system consisting of interfacing networks making it possible to transmit news on a pretty regular basis from one part of the Continent to another.